b)
[tex]3 \frac{6}{7} \times ( - \frac{1}{3} ) = \frac{27}{7} \times ( - \frac{1}{3} ) = \frac{9}{7} \times ( - \frac{1}{1} ) = - \frac{9}{7} = - 1 \frac{2}{7} [/tex]
c)
[tex]( - 2 \frac{2}{9} ) \times ( - 1.17) = ( - \frac{20}{9} ) \times ( - \frac{117}{100} ) = ( - \frac{1}{9} ) \times ( - \frac{117}{5} ) = \frac{117}{45} = 2 \frac{27}{45} [/tex]
d)
[tex](2 \frac{4}{5} ) ^{2} = 2 \frac{4}{5} \times 2 \frac{4}{5} = \frac{14}{5} \times \frac{14}{5} = \frac{196}{25} = 7 \frac{21}{25} [/tex]
Myślę że pomogłem ;)